Obramboslovna veja slovenske politologije - Bebler, Anton (Teorija in praksa, 2022)
In Slovenian social sciences elements of defence studies within political science have already existed before the Second World War, and after the war were mainly developed in the works of historians. In 1975, the establishment of the Chair of Defence Studies at the predecessor of today’s Faculty of Social Sciences brought about the institutionalisation of defence studies as an academic discipline. Ever since, defence studies as a discipline within political science have developed in the intertwinement with other social scientific disciplines, under the influence of a more developed Western military and political sciences, and in co-operation with international and professional associations. Until 1991, they were developed within the Yugoslav framewrok. Defence studies have been and remain closely related to educational and research activities of the Defence Research Center at the Faculty of Social Sciences in Ljubljana. They have actively contributed to the development of Slovenian political science and democratic political culture in Slovenia
Keywords: obramboslovje; Politične vede